Innovation and Economic Growth in the Top Five Southeast Asian Economies: A Decomposition Analysis - Hardi, Irsan; Ray, Samrat; Attari, Muhammad Umer Quddoos; Ali, Najabat; Idroes, Ghalieb Mutig (Heca Sentra Analitika, 2024)
Innovation has the potential to act as a double-edged sword in impacting economic growth. While it serves as a powerful driver of economic advancement, it also carries risks alongside its benefits. Recognizing this duality, our study aims to fill the identified gap and add comprehensiveness to the literature by assessing the individual impact of innovation indicators on economic growth in the top five Southeast Asian countries based on GDP: Indonesia, Thailand, Singapore, Malaysia, and Vietnam. The innovation aspect comprises 21 indicators from the Global Innovation Index (GII), grouped into seven categories: institution, human capital and research, infrastructure, market sophistication, business sophistication, knowledge and technology outputs, and creative outputs. Both panel analysis and country-specific assessments consistently conclude that innovation significantly influences economic growth. However, delving into the categorized indicators reveals intriguing insights. While all the indicators demonstrate a notable impact, most of them are found to hinder rather than foster economic growth. This compelling empirical evidence underscores that innovation in the selected countries has yet to be optimized, highlighting the urgent need to implement innovation-friendly policies, including removing innovation barriers, targeting investment in key sectors, and fostering education and skills development. This holistic approach aims to cultivate an environment conducive to innovation, thereby solidifying innovation's role as one of the primary drivers of economic growth.